Exploring EFL Learners’ Experiences in Developing Speaking Skills through TED Talks: A Narrative Inquiry - Irma Maulia; Sri Sumarni; Siti Drivoka Sulistyaningrum (The Study Program of English Education of Palangka Raya University, 2026)
English as a foreign language (EFL) learners are often faced with few opportunities to learn English meaningfully at work or university. Nevertheless, technological growth provides EFL learners with diverse media to acquire knowledge everywhere, supporting the development of English skills, particularly speaking skills. This qualitative study explores how TED Talks, as a medium, can support an EFL learner in enhancing her speaking skills. This research was conducted over 14 weeks using Narrative Inquiry as the method and was guided by a professional ELT teacher. The learning scenarios covered information from the TED Talks videos, selected according to the CEFR framework, which covered descriptors and speaking skills activities, including 3 Sustained Monologues: Describing Experience, Giving Information, and Putting a Case. The findings showed that the media contributes to the development of learners’ speaking skills from A1 to B1 levels, especially in comprehension, fluency, and vocabulary, with a total of 119 new vocabulary words. This study offers practical insights for EFL learners and teachers on how media helped learners’ speaking skills development. However, limited research has focused on developing speaking skills through TED Talks, highlighting the need for deeper exploration of overall production activities within the CEFR guidelines.